Immunomodulatory effects of apigenin, luteolin, and quercetin through natural killer cell cytokine secretion - Aung Myo Oo, Mohd Nasir Mat Nor, Ohn Mar Lwin, Nordin Simbak, Liyana Hazwani Mohd Adnan, Uthakar S Mahadeva Rao (Journal of Applied Pharmaceutical Science, 2022)
Nutritional immunology has attracted the interest of researchers due to its positive impact on health and immunity. By secreting cytotoxic granules and producing cytokines, natural killer (NK) cells are pivotal in fighting against viruses and cancer. Polyphenolic secondary metabolites, like flavonoids, have potent immunomodulatory effects by influencing cytokines. This study aimed to demonstrate the cytokine production of flavonoid-stimulated NK cells to find alternative immunomodulatory effects on immune cells. NK-92 cells were supplemented with three flavonoid compounds, apigenin, luteolin, and quercetin, overnight. An enzyme-linked immunosorbent assay was used to measure the levels of type-1 cytokines, interleukin-2 (IL-2), interferon-gamma, and type-2 cytokines, IL-4, and IL-10. Luteolin and quercetin treatment significantly increased NK cells’ IL-2 secretion but not apigenin. NK cell IFN-γ secretion was also significantly enhanced by luteolin at 25 µg/ml concentration. Nonetheless, at different doses, NK cell IL-4 and IL-10 secretions were unaffected by any of the three flavonoid compounds tested. Luteolin has the greatest effect on NK cell type-1 cytokine production, whereas quercetin only produces IL-2. Meanwhile, apigenin had no effect on type-1 and type-2 cytokine secretion. It is postulated that luteolin and quercetin modulate immune function through type-1 cytokines while having no effect on type-2 cytokine production.
Keywords: Apigenin, luteolin, quercetin, natural killer cells, cytokines, interleukins